Comparison of Ultrasound-Guided Nerve Block with Ultrasound-Guided Nerve Stimulation Technique for Obturator Nerve Block in Transurethral Resection of Bladder Tumour - Ahmad, Mirza Sijeel; Khan, Umer; Haider, Syed Aftab; Sultan, Atqua; Khanum, Shazia; Saleemi, Muhammad Saleem (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the ultrasound-guided nerve block with ultrasound-guided nerve stimulation technique for obturator nerve block (ONB) in patients undergoing transurethral resection of bladder tumour (TURBT). Study Design: Prospective comparative study. Place and Duration of Study: Department of Anesthesiology, Nishtar Medical University/Hospital Multan from Jan to Jul 2019. Methodology: A total of 80 patients were divided into two groups. In Group-I, an ultrasound-guided nerve block was applied, while in Group-II, an ultrasound-guided nerve stimulation technique was applied for the block. Time of onset/ success of motor block and ease of approach were the primary study endpoints. At the same time, the surgeon and patient satisfaction were secondary endpoints. Results: Motor block onset time was 6.58±2.16 minutes in Group-II versus 12.41±2.39 minutes in Group-I (p-value <0.001). Block performance time was 4.34±0.78 minutes in Group-II versus 2.09±0.46 minutes in Group-I (p-value <0.001). The block success rate was also higher in Group-II, with 36(90%) patients, compared to 31(77.5%) in Group-I, with an insignificant pvalue of 0.12. Surgeons were satisfied by the quality of the obturator nerve block in 37(92.5%) cases in Group -II and only 30 (75%) cases in Group-I (p-value 0.03). Conclusion: The ultrasound-guided nerve stimulator is superior to the Ultrasound-guided nerve block for Obturator nerve block (ONB) and is associated with higher patient and surgeon satisfaction.